ASSESSMENT OF THE PHYSICAL PROFILE AND PHYSIOLOGY OF FUTSAL ATHLETES - Desi Hari Subekti; Bayu Agung Pramono; Kunjung Ashadi; I Dewa Made Aryananda Wijaya Kusuma; Achmad Rizanul Wahyudi (STKIP PGRI Jombang, 2022)
Futsal is a sport that relies on optimal conditions, because this sport is carried out in a fast tempo of play in a short field area. The purpose of this study was to determine the physical and physiological profile of Sidoarjo spin one athletes as a reference for regional athletes in the same age group. The research method uses Quantitative Research with Descriptive method. 30 futsal athletes consisting of 15 male and female participated in this study. Statistical averages, standard deviations and percentages are used in analyzing the components of physical condition and physiological profile. Research using SPSS version 26 in lysing the data. The results showed that there was an overall difference that the physical abilities of male athletes were higher than those of female. This can be seen from the physical performance of male and female including flexibility of 22.7 cm (male) and 22.3 cm (female), balance of 66.9 seconds (male) and 42.4 seconds (female), stepping heights of 60.3 cm (male) and 41.5 cm (female), back muscle strength of 108.4 kg (male) and 67.5 kg (female), limb muscle strength of 123.1 kg (male) and 80.5 kg (female), abdominal muscle strength 25.5 times (male) and 24.3 times (female), power 66.2 cm (male) and 51.4 cm (female). Resting heart rate 69.4 beats/min (female) and 66.6 beats/min (male), VO2max 38.1 ml/kg/min (female) and 48.6 ml/kg/min (male), HRmax 185.2 beats/min (female) and 188.2 beats/min (male), 5th minute recovery 103.7 beats/min (female) and 103.3 beats/min (male). The conclusion of this study is that the balance of physical and physiological profiles will provide the best support in improving the performance of futsal athletes.